1367. Clinical Cure in Secondary Efficacy Populations in Patients With Complicated Urinary Tract Infection Treated With ZTI-01 (Fosfomycin for Injection): Findings From the ZEUS Trial. (26th November 2018) - Kaye, Keith; Rice, Louis B; Stus, Viktor; Sagan, Olexsiy; Fedosiuk, Elena; Das, Anita; Skarinksy, David; Eckburg, Paul B; Manvelian, Kristina; Ellis-Grosse, Evelyn J
Abstract: Background: ZTI-01 (fosfomycin for injection) is an investigational epoxide antibiotic with a differentiated mechanism of action (MOA) inhibiting an early step in bacterial cell wall synthesis. ZTI-01 has a broad spectrum of in vitro activit y, including multidrug-resistant Gram-negative pathogens, and is being developed for the treatment of patients with complicated urinary tract infection (cUTI) and acute pyelonephritis (AP) in the United States. Methods: ZEUS was a multicenter, double-blind, Phase 2/3 trial in hospitalized adults with cUTI and AP to evaluate safety and efficacy. Randomized patients received 6 g ZTI-01 q8h or 4.5 g IV piperacillin/tazobactam (PIP-TAZ) q8h for 7 days; patients with baseline bacteremia could receive up to 14 days; study continued to late follow-up (LFU, 26 ± 2 days). Oral step-down therapy was prohibited. ZTI-01 met the primary endpoint of noninferiority to PIP-TAZ. Secondary objectives included comparing clinical cure rates (assessed by investigator) in the modified intent-to-treat (MITT), microbiologic MITT (m-MITT), clinical evaluable (CE), and microbiologic evaluable (ME) populations at test-of-cure (TOC, Day 19 ± 2 days). Results: There were 464 patients randomized who received study drug. In all populations, clinical cure rates at TOC were high and similar between treatment groups (>90%) (table). Conclusion: These results demonstrate consistent efficacy in multiple secondary efficacy populations for patients with cUTI and AP who were treated with either ZTI-01 or PIP-TAZ. If approved by FDA, ZTI-01 may provide a new IV option with a differentiated MOA for patients in the United States with serious Gram-negative infections. 95% confidence intervals (CIs, two-sided) were computed using a continuity-corrected Zstatistic. Disclosures: K. Kaye, Zavante Therapeutics, Inc.: Scientific Advisor, Consulting fee. L. B. Rice, Zavante Therapeutics, Inc.: Scientific Advisor, Consulting fee. V. Stus, Zavante Therapeutics, Inc.: Investigator, Research support. O. Sagan, Zavante Therapeutics, Inc.: Investigator, Research support. E. Fedosiuk, Zavante Therapeutics, Inc.: Investigator, Research support. A. Das, Zavante Therapeutics, Inc.: Consultant, Consulting fee. D. Skarinksy, Zavante Therapeutics, Inc.: Employee and Shareholder, Salary. P. B. Eckburg, Zavante Therapeutics, Inc.: Consultant and Shareholder, Consulting fee. K. Manvelian, Zavante Therapeutics, Inc.: Employee and Shareholder, Salary. E. J. Ellis-Grosse, Zavante Therapeutics, Inc.: Employee and Shareholder, Salary.